Cross‐species transmission of feline herpesvirus 1 (FHV‐1) to chinchillas. Issue 6 (29th August 2022) - Shi, Longyan; Huang, Shuping; Lu, Yuxin; Su, Yuqing; Guo, Lin; Guo, Lijun; Xie, Wei; Li, Xiang; Wang, Yulong; Yang, Siyuan; Chai, Hongliang; Wang, Yajun
Abstract: Background: Herpesviruses are a class of double‐stranded DNA viruses found in both vertebrates and invertebrates. They are usually highly host‐specific and do not easily spread across species. Chinchillas have gradually entered the Chinese pet market in recent years, but references to viral infections in chinchillas are extremely scarce, and only two reports about the herpesvirus in chinchillas are available at present. Objectives: The aim of this study was to present the first report of FHV‐1 infection in chinchillas. Methods: A total of 130 nasopharyngeal swab samples of chinchillas and three nasopharyngeal swabs of domestic cats collected from a chinchillas farm were investigated by nested PCR for FHV‐1. Results: Four chinchillas were infected with FHV‐1, the positive rate was 3.08% (4/130), and two domestic cats were FHV‐1 positive (2/3). The 253 bp fragments of FHV‐1 gD gene from four chinchillas and two domestic cats were 100% identical, respectively, and the homology between chinchillas and domestic cat was 99.21%, but they all shared nearly 98.81% homology with the reference strain sequences. Phylogenetic tree analysis showed that these four chinchillas strains were clustered together with FHV‐1. Conclusions: This is the first time that FHV‐1 was detected in chinchillas and suggested chinchillas are susceptible to FHV‐1 and may play a role as a temporary reservoir for FHV‐1. Abstract : First report of Feline herpesvirus 1 (FHV‐1) infection in Chinchillas detected by nested PCR. The fragment (253bp) of FHV‐1 gD gene from chinchillas shared 98.81% homologous with the other FHV‐1 strains. And phylogenetic tree analysis showed that these chinchillas strains were clustered together with FHV‐1.